Perceived Risk Barriers to Internet Shopping - Aminu, Suraju Abiodun; Olawore, Olusegun Paul; Odesanya, Adesina Emmanuel (NIU Journal of Social Sciences, 2019)
In an e-commerce age, a large number of shoppers, browsing the Internet in Nigeria, still prefer to visit the traditional stores for shopping purposes despite the many benefits of Internet shopping. This paper examined the perceived risks that constitute barriers to Internet shopping for a large number of shoppers in Lagos State, Nigeria. We collected data from an online sample of 262 respondents through a questionnaire. The results of the multiple regression analysis supported all the three hypotheses of the paper, suggesting that perceived product risk, perceived time risk and perceived delivery risk negatively affected Internet shopping for our sample. We highlighted the implications of the findings for e-vendors operating in Lagos State and other states of the federation and made suggestions for future research direction. Keywords: Barriers, e-commerce, Internet shopping, online shoppers and perceived risk.